2006
DOI: 10.1080/14769670601092622
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language development in six infants adopted from China

Abstract: Children adopted from China currently represent the largest group of newly internationally adopted children in the US. An exploratory investigation of the communicative development of six young females adopted at ages 9 to 17 months from China by US families was conducted. Children were followed longitudinally from approximately three months post-adoption to age three years. English language skills were assessed at approximately three-month intervals, detailed communicative analyses were conducted at six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 55 publications
0
14
0
2
Order By: Relevance
“…3,7 Recent research has shown that the majority of children adopted from China as infants or toddlers learn English rapidly and few have delays that persist more than 2 years postadoption. 6,8 However, a small percentage experience significant difficulties learning English and are ultimately diagnosed with speech or language disorders. 6,8 A central question in research on speech and language development in IA children is how to determine at an early stage which children are likely to acquire English on their own given sufficient exposure and which will require intervention.…”
mentioning
confidence: 99%
“…3,7 Recent research has shown that the majority of children adopted from China as infants or toddlers learn English rapidly and few have delays that persist more than 2 years postadoption. 6,8 However, a small percentage experience significant difficulties learning English and are ultimately diagnosed with speech or language disorders. 6,8 A central question in research on speech and language development in IA children is how to determine at an early stage which children are likely to acquire English on their own given sufficient exposure and which will require intervention.…”
mentioning
confidence: 99%
“…Research indicates that expressive skills are lost within three months and receptive skills are lost within six months (Price, Pollock & Kimbrough 2006). The situation is different from a social and psychological perspective as the child arrives into a context where the adults are going to love and care and interact with this child as parents, with the child getting a lot of individual attention and over time developing an intimate secure attachment to the new parents.…”
Section: The Silent Period In Stages Of Second Language Developmentmentioning
confidence: 99%
“…However, data show relatively favourable developmental outcomes [30] that can be observed within several months following adoption, especially if it is done at an early age, i.e. in the first year or early in the second year of life [25,35].…”
Section: Effects Of Institutionalizationmentioning
confidence: 99%
“…Results of these studies suggest that neural systems which are crucial for the processing of social information can be adversely affected by early experiences, although an early placement in foster care may quickly enhance the progress in socio-cognitive skills [30]. on early communication and language and speech development The development of children raised in institutionalized settings has been repeatedly studied , e.g.…”
Section: Shared Characteristics Of Socially Deprived Subjects and Chimentioning
confidence: 99%
See 1 more Smart Citation